Operational transformation for dependency conflict resolution in real-time collaborative 3D design systems - Agustina (2013)
Conflict resolution is one major challenge in real-time distributed collaborative 3D design systems, which allow concurrent collaborative work on shared 3D documents. Operational Transformation (OT) is a core conflict resolution technique in a range of real-world collaborative systems. No existing OT technique is, however, capable of resolving conflicts among objects with dependency relations, i.e. an update of one object may propagate to other connected/dependent objects, which is commonly used in 3D or complex graphic design systems. This paper contributes a novel OT solution with such a capability for collaborative 3D design systems. This work is the first to extend OT capability to dependency conflict resolution, and OT application scope from 1D/2D to 3D applications, thus advancing the state-of-the-art of OT in both theory and practical application. The proposed solution has been theoretically verified for its correctness in detecting dependency conflicts and achieving consistent results, and implemented in the CoMaya collaborative design system.